Theological Studies of Paul's Teaching Based on 1 Thessalonians 4:13-18 For the Elderly Congregation in The church - Sihite, Franseda; Wahyuni , Sri; Sukarna, Timotius; Daliman, Muner (International Journal of Culture and Religious Studies, 2021)
The purpose of this study how to face death itself. For this reason, the readiness to accompany and teach about the overall condition of death and after death according to the Bible really makes a person ready to respond to a situation. The research used descriptive quantitative methods with field research study approach. This implementation of the Teaching of the Apostle Paul Preparing dying based on 1 Thessalonians 4:13-18 in the Elderly in the Church is in the category of being declared accepted. It is known from the results of calculations using Confidence Interval statistics at a significance level of 5% resulting in Lower Bound and Upper Bound 119.2812 - 122.0299. This shows that the Level of Implementation of the Teachings of the Apostle Paul Preparing dying based on 1 Thessalonians 4:13-18 in the Elderly in the Church is in the "medium" category. This is supported by the conclusions drawn from the first hypothesis compared with the results of calculations for each dimension (D1 - D3) as exogenous variables that show a more specific level of endogenous Variables that both state the level in the "medium" criteria.